Pengaruh Indikator Makroekonomi Terhadap Jumlah Tabungan Pada Bank Swasta Nasional di Indonesia - Esti R., Hedwigis; Ningsih, Sari (Business and Management Review, 2011)
This study aimed to analyze the effect of macroeconomic indicators of the amount of savings in the national private banks in Indonesia. The data used are secondary data from the total savings in private banks published in Banking Statistics Indonesia (SPI), reports of inflation and nominal interest rates of banks published by Bank Indonesia (BI) and GDP quarterly published by the Central Statistics Agency (BPS) for the period 2004-2008. The sampling technique used was saturated samples where all the population selected as a sample .. The results showed that the partial inflation rate has no effect on the amount of savings in private banks. While the nominal interest rate has a significant negative effect on the amount of savings and GDP has a significant positive effect on the amount of savings. Simultaneously three independent variables had a significant effect on the amount of savings.   Keywords: Inflation, nominal interest rates, GDP, savings.